Joseph Ratzinger’s Apologia for the Concept of the Soul - Borto, Paweł (Verbum Vitae, 2022)
This article aims to show the rationale behind Joseph Ratzinger’s defence of the concept of the soul in his theological reflection. Since Ratzinger did not produce a separate text justifying the need to maintain the concept of the soul yet justified it when discussing other issues, primarily those related to the Christian profession of faith, a distinction was made between biblical and philosophical-theological arguments to analyse his thought. The analysis indicated that J. Ratzinger saw two fundamental paths in the biblical tradition leading to the formation of the concept of the soul. The first is that which discovers God as the Life-Giver more powerful than death. The second involves the maturing of the profession of faith in the resurrection and the fact of Christ’s resurrection. The concept of the soul, to be developed later, will be based on these two fundamental truths attested to by the Bible and will be the drawing of anthropological conclusions originating in the most important truths of the faith, such as the resurrection of the body or belief in the Last Judgement. Ratzinger also examines other statements of the Church’s Magisterium or those handed down by philosophical and theological tradition from this standpoint. Hence, for him, the concept of the soul does not so much belong to particular anthropology as it derives from a profession of faith that calls for a clear and simple message that is not confined to the expert considerations of theologians.